Dhat Syndrome: Delay in Seeking Psychiatric Help, Cultural Myths and Co-Morbid Depression - Shakeel M Ansari; Shakila Mulla (National Journal of Community Medicine, 2017)
Introduction: Dhat syndrome is widely reported in India. Existing myths exaggerate this problem. Hence current study was conducted to assess role of myths in the course of dhat syndrome. Delay in seeking psychiatric help was also assessed and its association with co-morbid depression was analysed.